Reduction of Cortisol Levels in the Stress State of Diabetic Ulcer Post Amputation Patients by Quran Murattal Therapy in the Surgical Treatment Room Faisal Islamic Hospital Makassar - Zaenal; Rini Mustamin (Postgraduate, University of Mataram, 2025)
Amputation due to diabetic ulcers is one of the serious complications of diabetes mellitus which can result in significant psychological impacts for amputee patients experiencing anxiety disorders and depression. In the context of diabetic ulcers, where amputation often occurs in an attempt to save lives, feelings of anxiety and depression can increase significantly. This study uses an Experimental Quasy design, where this study aims to find out the effect of Qur'an Reading Therapy (TBA) on cortisol levels and anxiety levels in the state of stress after amputation of diabetic ulcers at Faisal Islamic Hospital Makassar. The sample size in this study was 30 respondents (15 treatment groups and 15 control groups). Data collection was carried out by means of a pre-post test with control group, In this study used the Wilcoxon Test paired t-test at the level of significance α = 0.05. Based on the results of the study, it was found that there was an effect of TBA on cortisol levels and anxiety response in postoperative patients (p=0.000). The conclusion in this study is the effect of Qur'an Reading Therapy (TBA) on cortisol levels and anxiety levels in the state of post-amputation of diabetic ulcers. Suggestion So that nurses can consider this therapy as one of the additional methods in managing diabetic amputee patients